Práticas de gestão e fomento ao empreendedorismo: lições das universidades públicas brasileiras mais empreendedoras - Alves, Juliani Karsten (2024)
Although universities play a crucial role in facilitating innovation and supporting entrepreneurship, there are still uncertainties about how these functions can be carried out more effectively. The gap in management practices and entrepreneurship promotion in Brazilian public universities, especially in the Innovation and Technology Centers (NITs), Agencies, and Vice-Rectories, raises the following research question: What practices are adopted by these structures in the most entrepreneurial Brazilian public universities to manage and foster the entrepreneurial process? To address this, the general objective of the study was to propose a framework of practices for the implementation and consolidation of entrepreneurship management and promotion in Brazilian public universities. This research is justified by the need to address the existing gaps in the study of Brazilian universities' practices in the field of entrepreneurship, a topic identified as a challenge in Brazilian Science and Technology Institutions (ICTs). The method employed in this qualitative research was a case study with five Brazilian universities that stand out in the field, involving data collection through documentary research and interviews. The data was analyzed using Bardin's (2011) content analysis technique. The practices observed in each of the institutions were analyzed across the 13 dimensions of the entrepreneurial university, followed by a joint analysis of the common practices across these institutions. The result of the study is embodied in a technological product: a manual as a practical and replicable tool for institutions interested in strengthening their entrepreneurial capacities. Additionally, by proposing a framework of practices, the research presented effective strategies for its implementation and consolidation, contributing to a reflection and change in posture among Brazilian public universities in response to new challenges. The manual integrates already established knowledge in a structured and practical way, combined and adapted uniquely to meet the specificities of entrepreneurship and innovation in the academic context.